The Collapse of Low-skill Male Earnings in the 1980s: Skill Mismatch or Shifting Wage Norms? - David R. Howell (Levy Economics Institute of Bard College, 1994)
The rapid growth in wage inequality and the rising incidence of low earnings in the 1980's can be traced in large part to the sharp decline in the real hourly wages of lowskill men. This paper examines alternative explanations for this wage collapse. A widely accepted story is that this collapse reflected declining demand (job opportunities) for low-skill jobs, a consequence of biased technological change. The result was skill mismatch: too few low-skill jobs for the low-skill workforce. The evidence described in this paper offers little support for this hypothesis; while substantial shifts in the skill mix of employment took place between 1973 and 1983, there was little skill restructuring after 1983. Crucially, however, it was in this latter period that we observe the highest rates of investment in computer-based technologies by firms in all sectors of the economy. An alternative "shifting wage norms" explanation is proposed. A survey of the evidence suggests that many employers began to adopt low-wage human resource strategies in the late 1970's. These employment practices undermined traditional wage-setting institutions (collective bargaining, internal labor market norms) that had protected low-skilled workers from the full force of labor market competition. In addition, these practices, together with unprecedented increases in the supply of low-skill foreign workers, resulted in a massive increase in the effective supply of labor competing for low-skill jobs. These developments led to a collapse of wages at the bottom of the wage distribution, a collapse facilitated by a 25 percent decline in the real value of the legal minimum wage in the 1980's.
Keywords: 330